Media Development Strategy Based on Audio Visual and Images in Improving Understanding of Soil Materials and Life Sustainability Concepts in Class IX - Maulia, Kiki Rizki; Doyan, Aris; Mahrus, Mahrus (International Journal of Science Education and Science, 2025)
Education plays a very important role in preparing quality human resources. The implementation of the independent curriculum encourages and challenges teachers to be creative in facilitating students to think critically, explore, be creative and experiment by utilizing various sources in the learning process. Researchers are interested in developing teaching materials in the form of teaching aids from used and practical materials for subsoil material and used as learning media in increasing students' conceptual understanding and also helping teachers in the learning process. This type of research is development. The development model used is the ADDIE model (props) and Lee and Owens (audio-visual media) with a 4-D model, namely define, design, develop, and disseminate. This media development strategy contains several characteristics, including (1) using Audio Visual media (2) containing sub-materials, videos, instructions and evaluation (3) facilitating students in developing students' thinking skills in a systematic, critical, logical, and analytical manner so that they can formulate their own learning conclusions with confidence; and (4) use language that is short, clear, easy to understand and understand, and uses supporting pictures related to land and the sustainability of life